Applying fuzzy inference system tsukamoto in crude palm oil company - Utami, Silvia Firda (2015)
Production planning is one of the important activities in the company, each of its activities involve decision making. To be able to meet the demand of its customers continuously, companies must have good planning. Therefore, this paper discusses the application of Fuzzy inference system Tsukamoto for decision making in production planning at the company's crude palm oil [CPO). The purpose of this research is to assist the production manager to determine the optimal number of CPO production, so that it can more effectively and efficiently. Data on production, inventory and demand in 2014 as inputs. There are three steps to solve the problem using FIS Tsukamoto i.e. Fuzzification, Inference and Defuzzification. The result obtained is the number of optimal inventory and production as well as higher profit